Endophytic Colonisation of Solanum lycopersicum and Phaseolus vulgaris by Fungal Endophytes Promotes Seedlings Growth and Hampers the Reproductive Traits, Development, and Survival of the Greenhouse Whitefly, Trialeurodes vaporariorum - Paradza, Vongai M.; Khamis, Fathiya M.; Yusuf, Abdullahi A.; Subramanian, Sevgan; Ekesi, Sunday; Akutse, Komivi S. (Frontiers in Plant Science, 2021)
In the scope of mitigating the negative impacts of pesticides use and manage the greenhouse whitefly, Trialeurodes vaporariorum sustainably, sixteen endophytic fungal isolates from five different genera (Beauveria, Trichoderma, Hypocrea, Bionectria and Fusarium) were screened for their ability to colonise two preferred host plant species, tomato (Solanum lycopersicum L.) and French bean (Phaseolus vulgaris L.) through seed inoculation. Seven and nine isolates were endophytic to P. vulgaris and S. lycopersicum respectively, where significant differences in endophytic colonisation rates were observed among the fungal isolates in P. vulgaris and plant parts, with a significant interaction between isolates and plant parts in S. lycopersicum. Hypocrea lixii F3ST1, Trichoderma asperellum M2RT4, Trichoderma atroviride F5S21 and Trichoderma harzianum KF2R41 successfully colonised all plant parts of both hosts therefore were selected and further evaluated for their endophytic persistence, effect on plant growth and pathogenicity to T. vaporariorum adults and F1 progeny. The four endophytes remained in both host plants for the five–week of assessment with varied colonisation rates related to strong interaction with time, isolate and plant part in both hosts. The effect of the same endophytes on the different host growth parameters varied in P. vulgaris and S. lycopersicum, with T. asperellum M2RT4 not boosting the growth in both host plants while T. atroviride F5S21 resulted in enhanced shoot biomass in S. lycopersicum. Trichoderma atroviride F5S21 and T. harzianum KF2R41 inoculated S. lycopersicum plants and Hypocrea lixii F3ST1, T. asperellum M2RT4 and T. harzianum KF2R41 inoculated P. vulgaris plants had significantly lower oviposition, while nymph development in both hosts was significantly prolonged in all the endophytically–colonised plants. The endophytes H. lixii F3ST1 and T. asperellum M2RT4 significantly reduced the longevity/survival of exposed T. vaporariorum adults and progeny in both S. lycopersicum and P. vulgaris. The findings demonstrate the attributes of the various endophytes in host plant growth promotion as well as their effects on the life–history parameters of T. vaporariorum and could consequently be developed as potential endophytic fungal–based biopesticides for sustainable management of the pest in S. lycopersicum and P. vulgaris cropping systems.